2022
DOI: 10.1186/s13195-022-01139-9
|View full text |Cite
|
Sign up to set email alerts
|

Persisting neuropsychiatric symptoms, Alzheimer’s disease, and cerebrospinal fluid cortisol and dehydroepiandrosterone sulfate

Abstract: Introduction Neuropsychiatric symptoms are important treatment targets in the management of dementia and can be present at very early clinical stages of neurodegenerative diseases. Increased cortisol has been reported in Alzheimer’s disease (AD) and has been associated with faster cognitive decline. Elevated cortisol output has been observed in relation to perceived stress, depression, and anxiety. Dehydroepiandrosterone sulfate (DHEAS) has known anti-glucocorticoid effects and may counter the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…More importantly, higher CSF cortisol and DHEAS levels predicted a more pronounced cognitive decline and disease progression over 36 months ( Ouanes et al, 2022a ). The higher CSF cortisol may reflect or contribute to more severe neuropsychiatric symptoms at baseline unrelated to AD pathology and more pronounced deterioration over 3 years ( Ouanes et al, 2022b ). These findings have important implications for identifying AD.…”
Section: Microbiome-based Ad Biomarkersmentioning
confidence: 99%
“…More importantly, higher CSF cortisol and DHEAS levels predicted a more pronounced cognitive decline and disease progression over 36 months ( Ouanes et al, 2022a ). The higher CSF cortisol may reflect or contribute to more severe neuropsychiatric symptoms at baseline unrelated to AD pathology and more pronounced deterioration over 3 years ( Ouanes et al, 2022b ). These findings have important implications for identifying AD.…”
Section: Microbiome-based Ad Biomarkersmentioning
confidence: 99%
“…In cerebrospinal fluid, altered cytokine levels have also demonstrated potential associations with NPS in AD—although findings warrant further investigation [ 95 ]. A single study has also reported on elevations in CSF cortisol and apathy in AD [ 96 ].…”
Section: Risk Factors For Apathy In Admentioning
confidence: 99%